The cycle structure of LFSR with arbitrary characteristic polynomial over finite fields - Chang, Zuling (2019)
We determine the cycle structure of linear feedback shift register with arbitrary monic characteristic polynomial over any finite field. For each cycle, a method to find a state and a new way to represent the state are proposed.